Interactive Learning of Arabic Grammar at Al-Azhar Course, Pare, Kediri, East Java - Khofifah, Khofifah; Nasiruddin, Nasiruddin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
Although many research has been conducted on interactive learning, there is still little that describes interactive learning of Arabic grammar in course institutions. Thus, this research aims to provide information about interactive learning of Arabic grammar at the Al-Azhar Pare Kediri, East Java course institute. The type of research carried out was qualitative research (Jailani, 2023) which was revealed by writing descriptive data reviewing several reasons for the implementation and interactive learning process of Arabic grammar at the Al-Azhar Pare Kediri course institute. Data was obtained through three techniques, namely observation, interviews and documentation. Data analysis was carried out through data reduction, data validity, source triangulation, data interpretation and conclusions. The results of the research show that there are several reasons for implementing interactive learning of Arabic grammar at the Al-Azhar Pare Kedi institution in East Java, namely, learning Arabic from native speakers, teachers who are graduates of the Middle East, having a pleasant learning class atmosphere, strategic location, there are superior programs and dormitories. The interactive learning process of Arabic grammar at the Al-Azhar Pare Kediri course institute includes reciprocity, balanced contribution, more than one way of solving problems, involving various sources, involving various skills, reading and writing and challenges. Learning Arabic in listening, reading, speaking and writing skills with an active receptive approach in informal and non-formal institutions can be carried out for further research. Recommendations from researchers are expected to be able to research in the Yellow Book Village of Pare Al-Azhar Kediri, East Java related to Balagoh science and the Al-Miftah Lil Ulum program for further research.